Pembuatan Bioplastik Berbasis Pati Ubi Jalar Dan Polyvinyl Alcohol (PVA) Menggunakan Graphene Sebagai Filler Dan Gliserol Sebagai Plasticizer - M. Fauzan Akbar; Amun Amri; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The aim of this research is to study the impact of graphene and glycerol addition on the mechanical properties, functional group, biodegrability, water uptake and morphology of the sweet potato and polyvinyl alcohol (PVA) based bioplastic. Bioplastics were synthesized using solution casting method with graphene addition of 0, 1, 2, 3%wt and glycerol addition of 20, 30, 40%wt into the sweet potato starch-PVA polyblend. Bioplastics were then tested their mechanical properties, morphology (SEM), functional group (FTIR), biodegrability, and water uptake analysis. The results showed that the addition of graphene increased the tensile strength, and the Young modulus, but decreased the elongation. Meanwhile, the addition of glycerol increased elongation, but decreased the tensile strength, and the Young modulus of bioplastics. The bioplastic produced using 3% of graphene and 20% of glycerol had the best mechanical properties with tensile strength of 16.76 MPa, elongation of 95.505%, and Young modulus of 17.549 MPa. Water uptake and biodegrability decreased as the increase of graphene content and increased as the increase of glycerol content. The sweet potato – PVA based bioplastic with the addition of graphene has a good perspective to develop further.Keywords : bioplastic, glycerol, graphene, mechanical properties, PVA, sweet potato starch